ANALISIS PENGARUH KEMAMPUAN KERJA, MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PT PLN (PeTseTo) UNIT INDUK PEMBANGUNAN JARINGAN JAWA BALI ( Studi Pada Kantor Induk) - Adhisti Asinta, 09.3502.0514; Darmi Astuti, Sih (Students Journal of Economic and Management, 2012)
The purpose of this study was to implementation to test and analyze the effect on the performance of employees working ability, motivation on employee performance and work environment on employee performance. The research was carried out at PT. PLN (Persero) Parent Unit Development and Networking of Java Bali in the parent olfice in Semarang, amounting to I l7 by using census method. The results of regression testing obtained results Adjusted R Square of 0.602, meaning that the change of the variable employee performance can be explained by the variable work ability, work motivation and work environment of 60, 2o/o. While fbr the F test showed that the ability to work together, work motivation and work environment aff-ects employeeperformance. Based on partial regression testing the ability of the mind to influence the perfbrmance of significance 0.006 <0.05, work motivation on perfbrmance with signilicance0.000 <0.05 and work environment efl-ects the perfbrmance of the significance 0.000. <0.05. It is identified that all the hypotheses accepted or proven Key words: Work Ability. Work Motivation, Work Environment and Employee Perfbrmance